IMPLEMENTASI RFID SEBAGAI DEBET CARD - Muh. Zainal; Muhammad Basri; Rahmat Hidayat (Jutkel: Jurnal Telekomunikasi, Kendali dan Listrik, 2020)
Along with the development of current technology, especially in the field of electronics and communication today. publicly developed parking management still applies a conventional parking system. Conventional parking has disadvantages including weak security and a lack of efficiency, seeing radio frequency identification is the right solution considering the current era is millennial, which always develops. RFID (Radio Frequency Identification) is a technology that combines the function of electromagnetic and electrostatic coupling in the portion of radio frequency from the electromagnetic spectrum, to identify an object. RFID technology is easy to use and is perfect for automatic operations. RFID combines advantages that are not available in other identification technologies RFID can be provided in devices that can only be read (Read Only) or can be read and written, do not require direct contact or light paths to operate, can function on a variety of environments, and provides a high level of data integrity.